Smart Materials and Design toward Safe and Durable Lithium Ion Batteries. Issue 11 (26th June 2019) - Wen, Lei; Liang, Ji; Chen, Jing; Chu, Zheng‐Yu; Cheng, Hui‐Ming; Li, Feng
Abstract: Smart electrochemical energy storage devices are devices that can operate autonomously to some extent. Although the conventional electrochemical energy storage devices, e.g., the commonly used lithium‐ion batteries (LIBs), may be externally monitored in terms of their voltage and current output to reflect the state of health for the devices, it is extremely important to exploit materials and devices that are intrinsically smart enough to be capable of rapidly self‐detecting and responding to faults, such as interior short circuits, overheating, abnormal capacity drop, and other types of mechanical/chemical damage. These "smart" features could significantly enhance the safety characteristics and durability of LIBs, which is essential for future usage. Therefore, recent achievements toward smart materials and design strategies for safer and more durable LIBs are summarized. The main categories are as follows: 1) New materials: This category mainly includes smart electrode materials with thermal/electrical/mechanical self‐response functions, and self‐response separators to suppress thermal runaway/lithium dendrite growth; 2) New chemistries: This category mainly includes electrolytes with reversible self‐protecting functions; and 3) New architectures with novel functions, such as shape‐recovery, self‐heating, and self‐monitoring. Besides the working mechanisms, the challenges that must be overcome for smart LIBs to be adopted in practical applications are also discussed. Abstract : Exploring smart and reversible ways to construct safer and more durable lithium‐ion batteries (LIBs) has become a major challenge for utilizing LIBs for future applications. By carefully selecting suitable smart materials, new battery chemistry, and new architectures, the LIBs can be endowed with one or more of desirable features, including self‐heating, self‐monitoring, self‐protecting, and self‐healing, to satisfy a wide range of current and future applications.